Pengaruh Faktor Kompetensi Individu dan Manajemen Kompensasi terhadap Kepuasan Kerja dan Kinerja Keuangan Daerah di Provinsi Sulawesi Utara - Johny Manaroinsong (Jurnal Aplikasi Manajemen, 2012)
This research explores the personal factor particularly the individual competence and management factor including the reward and punishment system related to the efficiency as marked by the work satisfaction and financial performance, and the local financial independence. For such purpose, the research applies quantitative analysis employing SEM analysis. This quantitative research takes an explanatory method orienting on structural equation modeling as a model for analysis. The population are the office leaders and UPTD of North Sulawesi Province comprising top, middle, and lower manager who are responsible for financial management. The sample is determined by way of multistage sampling. Based upon that particular consideration, The sample are 273 people randomly collected. Data are gathered by distributing questionnaire using Likert Scale model while Amos program is used for data analysis. The result shows that 1) the individual competence directly and significantly influences the performance of the local government in North Sulawesi both on the work satisfaction and financial performance, 2) the compensation management (reward and punishment system) directly and significantly influences the work satisfaction and financial performance, 3) the work satisfaction directly and negatively influences upon the financial performance yet it is not significant, 4) In North Sulawesi Province, the individual competence and management compensation influence the financial performance as indicated by the work satisfaction.Keywords: Individual competence, Compensation management, the local government’s financial performance